The impact of ethnocentrism on Serbian consumers - Veljković Saša (Marketing (Beograd. 1991), 2009)
The purpose of this paper is to examine the impact of consumer ethnocentrism on the intention to buy local products by Serbian consumers. Modern business trends and market changes are followed by new trends in consumer behaviour. Many changes in all segments of economy and society occurred in last few years in Republic of Serbia. Changes were especially influenced by: strong foreign competition, transition, change in values, economy and society liberalization, local culture, and as well by globalization and all other kinds of socioeconomic and psychological factors. The globalization of markets presents considerable challenges and opportunities for domestic and international marketers. All these have been influencing on people differentiation concerning ethnocentrism.